(untitled) (Fiep Bulletin - online, 2012)
Population ageing is a worldwide phenomenon, being the increase in life expectancy considered a positive factor, but that quality should be increased. Among the elderly hospitalization is high, being accurate to think of ways to provide quality assistance in that context, we consider all dimensions of this study sought to examine therefore the coping strategies and perceived social support for elderly hospitalized. For both, was developed a quantitative character field study, conducted in a hospital of high paraibano. The sample was composed of 30 elderly hospitalized, with ages ranging from 61 to 72 years, who answered an instrument composed of three parts: socio-demographic Issues, coping Scale and Scale of Social support, and the data were analyzed statistically. The main results have revealed that in relation to the coping strategy, seeking social support is the more significant for hospitalized elderly (M = 3.70). Given the above, it is concluded that it is important and essential in helping the elderly hospitalized take into consideration the psychological aspects, because these things have an important role in health. How to deal as a problem and social support are the factors that influence the patient’s suffering, either old or not. Thus, health professionals can play in seeking to provide support and assist that encompasses all dimensions of human being.